Addressing the crisis of congenital syphilis: Key findings from an evaluation of the management of syphilis in pregnancy and the newborn in South‐East Queensland. (31st August 2021) - Wu, Mandy; Seel, Mandy; Britton, Sumudu; Dean, Judith A.; Lazarou, Mattea; Safa, Huda; Griffin, Paul; Nourse, Clare
Abstract : Background: Syphilis in pregnancy and congenital syphilis (CS) are increasing in Australia. Prevention of adverse outcomes requires adherence to management guidelines. Aims: The aim is to evaluate the management of syphilis in pregnant women and their newborns. Materials and Methods: A retrospective study of public health notifications, clinical records and testing results of women with positive syphilis serology in pregnancy requiring treatment from 2016 to 2018 inclusive across South‐East Queensland was conducted. Management was described and compared with contemporary guidelines from the Australasian Society of Infectious Diseases, the Communicable Diseases Network Australia and the United States Centers for Disease Control and Prevention. Results: Of 30 women identified, 22 (73%) had management consistent with the guidelines (stage‐appropriate penicillin regimen, appropriate dosing interval and treatment completed greater than 30 days before delivery). Only 14 (47%) women had documentation of partner testing and/or treatment. Of 26 mother–infant pairs with complete data, 16 (62%) had investigations at delivery consistent with recommendations (parallel maternal–infant rapid plasma reagin, infant syphilis immunoglobulin M, placental histopathology +/– syphilis polymerase chain reaction and infant clinical examination). One infant met the criteria for confirmed CS. Five infants received penicillin therapy. Only seven (27%) infants had serological monitoring after discharge. Conclusions: Management can be optimised with timely maternal testing and treatment, comprehensive partner screening and treatment, strict adherence to seven‐day penicillin dosing for late latent syphilis and thorough maternal and infant testing after treatment and delivery. If maternal treatment was inadequate in pregnancy, consideration needs to be given to close evaluation and empiric treatment of the infant.